1993
DOI: 10.2307/2986177
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Systematic Sampling of Land Use

Abstract: SUMMARY In this paper two‐dimensional systematic sampling of land use is considered. Data for two study areas which provide a complete enumeration of land use, and which are held in digital form, are a basis for a series of sampling experiments. First, the efficiency of systematic sampling is compared with other schemes. Second, these results are related to the autocorrelation functions of the data. Third, methods for estimating sampling error from a single sample are assessed. The results reported here confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 16 publications
1
39
0
1
Order By: Relevance
“…Cochran ( 1946, see also Iachan 1982 analytically proved that a systematic design is more precise for linear populations whose spatial autocorrelation declines exponentially with separation distance. Examples of systematic designs bringing higher survey precision in spatially autocorrelated populations were reported in a range of applied ecological contexts (e.g., Dunn and Harrison 1993, Ambrosio et al 2004, Aune-Lundberg and Strand 2014 and in the application of Euclidean distance analysis to animal habitat selection analysis (Benson 2013 ) and in stereology (Gundersen et al 1999 ).…”
Section: True Precision Of Random and Systematic Survey Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochran ( 1946, see also Iachan 1982 analytically proved that a systematic design is more precise for linear populations whose spatial autocorrelation declines exponentially with separation distance. Examples of systematic designs bringing higher survey precision in spatially autocorrelated populations were reported in a range of applied ecological contexts (e.g., Dunn and Harrison 1993, Ambrosio et al 2004, Aune-Lundberg and Strand 2014 and in the application of Euclidean distance analysis to animal habitat selection analysis (Benson 2013 ) and in stereology (Gundersen et al 1999 ).…”
Section: True Precision Of Random and Systematic Survey Designsmentioning
confidence: 99%
“…More recent statistical investigation (D ' Orazio 2003, Wolter 2007 ) assumed systematic sampling to be more precise in autocorrelated populations and focused on the still unsolved problem of how to reliably estimate the variance of the estimate of the mean from a systematic survey for linear (Wolter 1984(Wolter , 2007 and two-dimensional (i.e., spatial) populations (D ' Orazio 2003 ). Published studies in the applied ecological literature have now shifted to general agreement that systematic designs are more precise in spatially autocorrelated populations (e.g., Dunn and Harrison 1993, Ambrosio et al 2004, Aune-Lundberg and Strand 2014.…”
Section: Introductionmentioning
confidence: 99%
“…32). Dunn & Harrison (1993) used a similar variance estimator in a simulation study and showed that it outperformed the random sample variance estimator (Eq. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Milne (1959) and Ripley (1981) suggest that treating the sample as random remains a reasonable approach, and that the usual variance estimator u provides satisfactory performance. However, Payandeh (1970) and Dunn & Harrison (1993) caution that this approach can seriously overestimate the sampling error and that a systematic sample variance estimator should be used.…”
Section: Discussionmentioning
confidence: 99%
“…Variances were calculated using a systematic sampling variance estimator described by Millar & Olsen (1995). Simple random sampling variance can overestimate the sampling error in systematic surveys (Dunn & Harrison 1993), because the quadrat position is not random, but is directly related to the position of the first quadrat.…”
Section: Population Estimatesmentioning
confidence: 99%